2009
DOI: 10.1186/cc7164
|View full text |Cite
|
Sign up to set email alerts
|

Renal haemodynamic, microcirculatory, metabolic and histopathological responses to peritonitis-induced septic shock in pigs

Abstract: Introduction Our understanding of septic acute kidney injury (AKI) remains incomplete. A fundamental step is the use of animal models designed to meet the criteria of human sepsis. Therefore, we dynamically assessed renal haemodynamic, microvascular and metabolic responses to, and ultrastructural sequelae of, sepsis in a porcine model of faecal peritonitisinduced progressive hyperdynamic sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
1
11

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(91 citation statements)
references
References 36 publications
4
74
1
11
Order By: Relevance
“…SAKI can occur in the presence of normal or even increased renal blood flow (8). An intact renal blood flow does not guarantee adequate microvascular perfusion (9). Intrarenal blood flow may also considerably differ between medulla and cortex area (10).…”
Section: Gordon Et Al Recently Reported the Results Of The Multicentmentioning
confidence: 99%
“…SAKI can occur in the presence of normal or even increased renal blood flow (8). An intact renal blood flow does not guarantee adequate microvascular perfusion (9). Intrarenal blood flow may also considerably differ between medulla and cortex area (10).…”
Section: Gordon Et Al Recently Reported the Results Of The Multicentmentioning
confidence: 99%
“…La importancia de la caída en la presión de perfusión renal como mecanismo de IRA ha sido destacada previamente por otros autores 16,17 . En particular, el estudio de Chvojka et al 16 muestra que en animales sépticos, la existencia de IRA se correlacionó principalmente a una disminución en la presión de perfusión renal.…”
Section: Discussionunclassified
“…In addition, previous studies demonstrated that a decrease in total RBF alone cannot entirely account for the reduction in GFR and that the heterogeneity of the blood flow distribution between cortex (glomeruli) and the medulla (tubule) with regional shift of blood to medulla could be of greater importance during an episode of AKI 14,15 .…”
Section: Critical Reviewmentioning
confidence: 99%
“…Chvojka et al observed 14 that the renal microcirculation changes during sepsis induced AKI could be total or at least partially independent of the renal macrocirculation. In particular, Wang group 19 have found that capillary leakage is the early measured microvascular change (2 hrs after sepsis), even before any measured reduction in RBF and peritubular capillary perfusion, and suggested that renal microcirculatory failure and direct tubular injury, even after correction of systemic hemodynamics, contribute significantly to sepsis-induced AKI in humans.…”
Section: Microcirculation and Akimentioning
confidence: 99%